Menjadi Pribumi di Negeri Orang: Pergumulan Identitas Masyarakat Arab di Indonesia - Jahroni, Jajang (Studia Islamika, 2000)
This book presents a discussion of the historical process of how Arab communities in Indonesia have dealt with their identities. The book primarily focuses on the early 20th century period, when Arab communities in Indonesia encountered rapid and fundamental social, cultural and political change. Modernization in Indonesia, under the influence of colonialization, changed people's consciousness of their social and political structure which in turn, affected the way they articulated their identities. The concept of nationalism emerged in the early 20th century. It was often interpreted. by Indonesian people along ethnic lines, thus accelerating the process of defining Arab identity.DOI: 10.15408/sdi.v7i3.706